1997
DOI: 10.1007/s004030050219
|View full text |Cite
|
Sign up to set email alerts
|

The demonstration of serum interleukin-8 and superoxide dismutase in Adamantiades-Behçet's disease

Abstract: Serum interleukin-8 (IL-8) production was measured in 43 Adamantiades-Behçet's disease (A-BD) patients and in 46 healthy volunteers using a sandwich enzyme-linked immunosorbent assay (ELISA). The mean serum IL-8 level of the patients (14.6 +/- 3 pg/ml) was significantly higher than that of controls (10.8 +/- 3 pg/ml, P < 0.05). Since IL-8 is known to have proinflammatory properties, it may play some role in the pathogenesis of A-BD. We also investigated the activity of serum superoxide dismutase (SOD) in the 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 6 publications
2
42
0
2
Order By: Relevance
“…Various investigations on BD have reported the increased serum IL-8 [2,14,22,29] and spontaneous production of IL-8 by peripheral mononuclear cells [18,30] in BD. One recent report even suggested that serum IL-8 can be a more reliable marker of the disease activity, according to the number of actively involved organs, than C-reactive protein (CRP) or erythrocyte sedimentation rates (ESR) in BD [14].…”
Section: Introductionmentioning
confidence: 99%
“…Various investigations on BD have reported the increased serum IL-8 [2,14,22,29] and spontaneous production of IL-8 by peripheral mononuclear cells [18,30] in BD. One recent report even suggested that serum IL-8 can be a more reliable marker of the disease activity, according to the number of actively involved organs, than C-reactive protein (CRP) or erythrocyte sedimentation rates (ESR) in BD [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, no laboratory marker has been widely accepted for following up the activity of the disease in clinical and therapeutic studies. Interleukin-8 (IL-8) has recently been under focused investigation because of its possible participation in the evolution of the disorder [4, 5, 6, 7, 8, 9]. Although IL-8 is not a specific marker for Adamantiades-Behçet’s disease, cumulative evidence suggests a significant correlation between disease activity and increased serum levels of IL-8 [4, 9].…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies, different SOD levels have been reported for BD patients [25,26]. Wang et al [25] reported increased SOD activity in the active phase of BD, whereas other researchers found decreases [26]. Kiraz et al [24] reported that plasma SOD activities of BD patients were not different from those of controls.…”
Section: Discussionmentioning
confidence: 99%